Locus Coeruleus Neuronal and Behavioral Activity Following Acute and Chronic Methylphenidate - Tang, Bin; Dafny, Nachum (Journal of Brain Sciences, 2015)
Methylphenidate (MPD) is one of the choices to treat attention-deficit / hyperactivity disorder (ADHD), and its mechanism of action is not clear. Concomitant behavioral and locus coeruleus (LC) neuronal activity were recorded following acute and chronic (0.6, 2.5 and 10 mg/kg) MPD in freely moving rats. The experiment last for 10 days. (1) The behavioral recording showed that acute MPD increases in locomotor activity in a dose dependent manner. (2) The same dose of chronic MPD administration elicits in some animals behavioral sensitization and in others behavioral tolerance. (3) The majority of the LC unit responded to acute MPD exposure by increase their firing rate. (4) The baseline activity on experimental day 10 (ED 10) after six daily repetitive MPD exposure was modulated in most of the LC units. (5) More than 90% of the LC unit respond to chronic MPD exposure and the majority of them by decrease their firing rate compared to the initial MPD effect. (6) The neuronal response to acute and chronic MPD recorded from animals expressing behavioral sensitization was significant difference from the LC units recorded from animals that expressed behavioral tolerance. Results indicated that the LC neuronal activities may contribute to the expression of behavioral sensitization and tolerance induced by chronic MPD administration and suggested that it is essential to record the animal’s behavioral responses concomitantly with the LC neuronal activity events.